Misuse case modeling for secure e-tendering system - Mohd, Haslina; Muhammad Robie, Mohd Afdhal; Baharom, Fauziah; Nordin, Nazib; Muhd Darus, Norida; Saip, Mohamed Ali; Yasin, Azman; Zainol, Azida; Hashim, Nor Laily (2012)
Tendering process is utilized by principal to invited capable tenderer to participate in competitive bid for winning a large project.Due to advent of IT infrastructure, E-tendering is introduced and adopted in many countries. Yet, an electronic environment did not promise curbing collusion between principal and certain tenderers. Other than common threats to system like security breaches by malicious parties, security issue related to ethical issue like fraud and repudiation issue where no evidence existed to denied it.In this paper, common threats for e-tendering process altogether with security countermeasure are described. This three interrelated attribute (consist of tender phase, threat and security countermeasure) are illustrated in misuse case for better understanding of the risk that may occurs in particular tender phase. Furthermore, it sought to ease the system developer for designing and constructing a secure e-tendering system.